2020
DOI: 10.1248/bpb.b20-00361
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Concomitant Administration of Vonoprazan Fumarate on the Tacrolimus Blood Concentration in Kidney Transplant Recipients

Abstract: Vonoprazan fumarate (vonoprazan) is a new kind of acid suppressant with potent acid inhibitory effects. Therefore, it has been administered to kidney transplant recipients for treatment or prophylaxis of steroid ulcers, refractory peptic ulcers, and gastroesophageal reflux disease. Because tacrolimus, which is a well-established immunosuppressant for kidney transplantation, and vonoprazan share the CYP3A4 system for metabolism, drug interactions are anticipated upon simultaneous administration. We retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
3
1
Order By: Relevance
“…Therefore, vonopranan is considered to produce DDIs with tacrolimus in kidney transplant recipients under tacrolimus-based immunosuppressive therapy. A similar result has been reported in another study in which the C/D ratio of tacrolimus increased 1.1-fold after switching rabeprazole to vonoprazan in outpatients 2-7 years post-transplantation [27].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Therefore, vonopranan is considered to produce DDIs with tacrolimus in kidney transplant recipients under tacrolimus-based immunosuppressive therapy. A similar result has been reported in another study in which the C/D ratio of tacrolimus increased 1.1-fold after switching rabeprazole to vonoprazan in outpatients 2-7 years post-transplantation [27].…”
Section: Discussionsupporting
confidence: 88%
“…This may be a potential bias for the study setting. The increase in C/D ratio of tacrolimus after switching of rabeprazole to vonoprazan was large (41.8%) compared with previous studies by Mei T. [27] and Watari S. [30], which showed a 10.6% increase and no increase after the conversion, respectively, in the outpatient phase of posttransplantation. To confirm this difference, the data for a larger number of the patients is required in the early phase of post-transplantation.…”
Section: Discussioncontrasting
confidence: 54%
“…A recently published retrospective cohort study in a single center (n = 52) showed that blood concentrations of tacrolimus increased with a statistical significance following conversion from rabeprazole to vonoprazan, but the change was ignorable [14]. They used tacrolimus trough concentration/tacrolimus dose (ng/mL)/(mg/day).…”
Section: Discussionmentioning
confidence: 99%
“…Rabeprazole is slightly metabolized by CYP2C19, whereas vonoprazan is hardly metabolized by CYP2C19 [14]. Patients in the CYP2C19 extensive and intermediate metabolizer subgroups are predicted to partially metabolize rabeprazole by CYP2C19 and thus should not have experienced significant antagonism on the CYP3A4 enzyme prior to conversion to vonoprazan.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that CGRP expression was significantly increased in the esophageal mucosa of patients with CGRP and negatively correlated with patient's nociceptive threshold. Capsaicin receptors are highly expressed in the esophageal tissue of RRE patients and acid exposure stimulates the release of CGRP from esophageal nerve endings, thus increasing the sensitivity of the patient's esophageal mucosa to acid or mechanical stimuli [23] . Therefore, CGRP is closely related to visceral sensitivity in patients with RRE.…”
Section: Resultsmentioning
confidence: 99%